2014
DOI: 10.4328/jcam.1254
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of the Epidemiological Markers of Allergy in Adults

Abstract: were recorded. Results: Total Ig E level was 307.6 ± 14.5 kU/L. Age of 25.6 % of the patients was between 30-39 years. The most common irritant that exacerbates the allergic rhinitis and asthma symptoms was air pollution (%77.0) and house dust ranks second (%76.2). The SPT of the cases were evaluated taking the age groups into account and this revealed an decreased rate of positivity to the prick test for plants and cereals with increasing age (p<0.001). Among smokers grass, mold ,epidermal prick positivity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Allergen-specific immunotherapy (SIT) has the advantage of being the only causal treatment of allergic controlled asthma and rhinitis but is fraught with the dangers of severe systemic or local adverse effects and anaphylaxis [ 19 – 21 ]. Allergic diseases are probably due to complex interactions between largely unknown genetic and environmental factors.…”
Section: Combination Therapy With Omalizumab and Allergen Immunotheramentioning
confidence: 99%
“…Allergen-specific immunotherapy (SIT) has the advantage of being the only causal treatment of allergic controlled asthma and rhinitis but is fraught with the dangers of severe systemic or local adverse effects and anaphylaxis [ 19 – 21 ]. Allergic diseases are probably due to complex interactions between largely unknown genetic and environmental factors.…”
Section: Combination Therapy With Omalizumab and Allergen Immunotheramentioning
confidence: 99%
“…In our previous study [2] in Antalya between March, 2010 and February, 2011 showed that mediterranean region has a flora that includes a variety of grass, plants and trees that are known to cause allergic diseases. During these months, it is windy with without rain and lukewarm temperatures, all of which are contributing factors for seasonal allergies [3,4]. During the period of March,2011 and February,2012, we examined 982 patients with allergic rhinoconjunctivitis and allergic asthma.…”
mentioning
confidence: 99%